Barriers and facilitators to implementation of interventions to mitigate moral injury among nurses - Godzik, Cassandra M.; DiBenedetto, Jennifer K.; Usset, Timothy J.; Stiles, Heather; Klein, Heather; Fortuna, Karen; Pepin, Renee; Wright, Hannah; Locke, Amy; Thomason, Helen; Smith, Andrew J. (Frontiers in Health Services, 2025)
BackgroundIn the post-pandemic recovery era, addressing moral injury is critical due to high prevalence and impact on mental and occupational health. Interventions that address moral injury in hospital settings are limited. Further, engaging HCWs in any mental health interventions has proven challenging for a variety of reasons and exacerbated by factors such as a rural setting. Implementation science aimed at understanding barriers and facilitators to interventions is needed in order to build and offer interventions that are usable, feasible, acceptable, and effective. The current study aimed to understand such barriers and facilitators to building moral injury interventions for nurses on the medical intensive care unit (MICU).MethodsWe conducted semi-structured qualitative interviews using the Consolidated Framework for Implementation Science Research (CFIR) and Peer and Academic Model of Community Engagement with 25 participants in a rural hospital system, 19 nurses currently working in the MICU and six nurses who left their MICU employment. Interviews were transcribed and analyzed using a thematic analysis approach.ResultsThere were five CFIR domains and 14 associated CFIR constructs that impacted intervention implementation in this population. Barriers included resource costs, skepticism regarding the effectiveness of new resources, lack of support from leaders, concerns that emotions affect professional image, inability to take breaks, and a disconnect between nurses' lived experiences and community perceptions. Facilitators included interventions specifically tailored for the MICU, strengths in teaming and social support among fellow nurses, and a desire for change because of factors such as a high turnover rate. Participants also highlighted a strong motivation to provide the best care possible and a desire to build resilience by supporting each other.ConclusionAnalysis of barriers and facilitators suggests value in improving the opportunities for HCWs to process morally injurious experiences with interventions specific to a particular unit and resources such as peer support and chaplains. There is a demonstrated need for high-level organizational change to address the dynamic needs of our nurses.